Actas da videojogos 2020 - Barbedo, Inês (2022)
The 12th Edition of the International Conference on Videogame Sciences and Arts, Videojogos2020, is a joint organization of the School of Public Management, Communication and Tourism – Polytechnic Institute of Bragança (EsACT – IPB) and the Portuguese Society of Videogames Sciences (SPCV). This year, due to the pandemic context, activities were conducted online.